Toward professional practice: student learning opportunities through participation in engineering clubs. (2nd November 2019) - Hinkle, Christopher M.; Koretsky, Milo D.
ABSTRACT: Clubs constitute a prominant co-curricular activity to prepare students for effective professional careers, yet the role of engineering clubs in students' professional formation is poorly understood. This qualitative, comparative case study investigated three student engineering clubs at a large American public university. The clubs included a domestic chemical reaction car competition; a formula racing club that partners with a German team and competes both domestically and internationally; and a humanitarian engineering club centred on service learning projects in developing countries. Data collection included semi-structured interviews with participants ( N  = 19) and observations of club work sessions ( N  = 27). Using Cultural Historical Activity Theory (CHAT) as the analytical framework, the transcribed interviews were coded to characterise the activity in each club. The findings demonstrate that a confluence of elements, especially decision-making rules and division of labour, leads to a fundamentally distinct activity system in each club. Consequently, each club differs in the ways it influences students' professional formation. More generally, this study illustrates the potential of CHAT for analysis of co-curricular activity that can lead to alternative approaches to activity design.